Chronic active Epstein-Barr exacerbated by COVID-19 co-infection - David B Villafuerte; Olga Lavrynenko; Rayan Qazi; Marco F Passeri; Fernando L Sanchez (International Journal of Infectious Diseases, 2022)
A 60-year-old Hispanic female was admitted with recurrent fevers, altered mental status, lymphadenopathy, hepatosplenomegaly, and pancytopenia. Initially, sepsis was presumed because of recurrent urinary tract infection with extended-spectrum beta-lactamase Escherichia coli. Despite appropriate therapy, her clinical condition continued to decline. An extensive workup was obtained to determine the source of her ailments. Bone marrow biopsy was negative for leukemia, lymphoma, and myelodysplastic syndrome; fluorescence in situ hybridization and a cytogenetic panel were normal; a lumbar puncture was negative. However, peripheral blood was remarkable for elevated titers for Epstein-Barr virus (EBV) consistent with chronic active EBV. Treatment with valganciclovir showed early positive results, but the patient became co-infected with COVID-19, and her EBV titer increased again, resulting in a precipitous health decline and death.